Millennials’ Interest in Using OVO Applications in Asahan District in the Perspective of Islamic Law - junaidi, ahmad; Dewi, Nurul Aulia (LAA MAISYIR : Jurnal Ekonomi Islam, 2022)
The purpose of this research is to find out and analyze the interest of the people of Asahan Regency in the use of OVO products. This study uses a quantitative descriptive approach with a sample of 73 respondents belonging to millennials. From the results of the research above, it can be concluded that the potential for developing E-Money in Millennials can be developed because of the results of research that has been carried out the percentage of interest in using OVO E-Money is at a moderate level with a percentage of 45% and a high interest in using OVO is 27%. This can trigger the use of OVO E-Money with marketing programs and target markets from OVO itself. Keywords : Development, E-Money, Milenial